STRATEGI PEMBELAJARAN PENDIDIKAN PANCASILA DALAM MENINGKATKAN SIKAP TOLERANSI SISWA DI LINGKUNGAN SEKOLAH SMA SRIJAYA NEGARA - Agra Alfareza; Emil El Faisal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of Pancasila education learning strategies in improving students' tolerance attitudes at SMA Srijaya Negara Palembang. Using a qualitative approach with descriptive methods, the research involved 5 informants consisting of 3 grade X students, 1 Pancasila education teacher, and 1 homeroom teacher. Data collection techniques were conducted through participatory observation, in-depth interviews, and documentation. Data analysis used an interactive analysis model with stages of data reduction, data presentation, and conclusion drawing. The research results show that Pancasila education learning strategies have been effective in improving students' tolerance attitudes with a success rate of 88.89% categorized as